Addressing the Mapping Problem in Sonic Information Design through Embodied Image Schemata, Conceptual Metaphors, and Conceptual Blending - Roddy, Stephen (My University, 2018)
This article explores the mapping problem in parameter mapping sonification: the problem of how to map data to sound in a way that conveys meaning to the listener. We contend that this problem can be addressed by considering the implied conceptual framing of data–to–sound mapping strategies with a particular focus on how such frameworks may be informed by embodied cognition research and theories of conceptual metaphor. To this end, we discuss two examples of data-driven musical pieces which are informed by models from embodied cognition, followed by a more detailed case study of a sonic information design mapping strategy for a large-scale Internet of Things (IoT) network.
Keywords: Auditory Display; Image Schema; Conceptual Blending; Sound; Data-Driven; Music; Music Cognition; Sonification; Conceptual Metaphor; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Smart & Sustainable Planet; Auditory Cognition; Auditory Display; Human-Computer Interaction; Internet of Things; Smart Cities; Sonification; cognition; Communication; Culture